Fatigue properties of a nanocrystalline titanium based bulk metallic glassy alloy - Okayasu, Mitsuhiro (Elsevier, 2019)
To obtain a better understanding of the fatigue properties and crack growth characteristics of a nano-crystalline titanium based bulk metal glasses (Ti-BMG) made by vacuumed casting process, the fatigue failure mechanisms of Ti-BMG have been investigated viaSeNand da/dNeDKtests. For comparison, the crystalline Ti alloy Ti-Al6V4 was also employed. The fatigue strength in the early fatigue stage was high for Ti-BMG due to the high tensile strength. However, the fatigue strength decreased significantly in the late fatigue stage. The higher slope ofSeNrelation was detected for Ti-BMG, which crossed that for the Ti-Al6V4 sample around 5 10 3 cycles. In the higher Region II, the fatigue crack growth rate was of similar level for both Ti-BMG and Ti-Al6V4 due to their similar strain energy. In the lower Region II, however, the lower crack growth resistance was obtained for Ti-BMG, as compared to Ti-Al6V4. This was attributed to the high crack driving force for Ti-BMG, caused by the weak roughness-induced crack closure. Such crack closing characteristics of Ti-BMG were systematically investigated by various experimental techniques